STATUS DAN PERUBAHAN INDIKATOR VITALITAS HUTAN KONSERVASI TAMAN HUTAN RAYA WAN ABDUL RACHMAN: Status and Changes of Forest Vitality Indicators in Forest Conservation Taman Hutan Raya Wan Abdul Rachman (PERENNIAL, 2021)
Forests can provide many benefits both from an ecological, economic, and social perspective. These benefits can be achieved through sustainable forest management. Forest health is one of the criteria for sustainable forest management. Forest health can be assessed through monitoring forest health. One of the ecological indicators that can be used to monitor forest health is an indicator of vitality. This study aims to determine the value of status and changes in vitality indicators by using tree damage parameters and crown conditions. Status values ​​and changes in vitality indicators are needed in order to make different forest management decisions. This research was conducted in Tahura Wan Abdul Rachman (Tahura WAR) Plant and Animal Collection Block using Forest Health Monitoring (FHM). This research was conducted twice, the first measurement was carried out in May 2019, and the second measurement was carried out in December 2020. The results showed that the value of changes in the vitality indicator tends to increase. The first measurement of the status of the vitality indicator 50% is in the "medium" category, 25% is in the "good" category, and 25% is in the "bad" category. The status of the vitality indicator in the second measurement is 50% in the "good" category and 50% in the "bad" category. This change can be caused by an increase in tree damage in each cluster plot. The management decision for the Tahura WAR Plant and Animal Collection Block is that it is necessary to change the management pattern.